The political and economic instability of dilma Rousseff’s second government in Brazil: Between impeachment and the pragmatic turn - Pereyra Doval, María Gisela (2016)
This article aims to describe the political and economic tensions experienced by Brazil, six months into the second term of President Dilma Rousseff. It also analyses whether the head of state can be subjected to political trial/impeachment as a result of corruption charges, and attempts to explain the government’s strategy to try to get out of the quagmire by means of a pragmatic twist, away from the premises of the electoral campaign.